Uncharted Diversity and Ecology of Saprolegniaceae (Oomycota) in Freshwater Environments - Bora Nam; Thuong T. T. Nguyen; Hyang Burm Lee; Sang Kyu Park; Young-Joon Choi (Mycobiology, 2022)
AbstractThe fungal-like family Saprolegniaceae (Oomycota), also called “water mold,” includes mostly aquatic saprophytes as well as notorious aquatic animal pathogens. Most studies on Saprolegniaceae have been biased toward pathogenic species that are important to aquaculture rather than saprotrophic species, despite the latter’s crucial roles in carbon cycling of freshwater ecosystems. Few attempts have been made to study the diversity and ecology of Saprolegniaceae; thus, their ecological role is not well-known. During a survey of oomycetes between 2016 and 2021, we investigated the diversity and distribution of culturable Saprolegniaceae species in freshwater ecosystems of Korea. In the present study, members of Saprolegniaceae were isolated and identified at species level based on their cultural, morphological, and molecular phylogenetic analyses. Furthermore, substrate preference and seasonal dynamics for each were examined. Most of the species were previously reported as animal pathogens; however, in the present study, they were often isolated from other freshwater substrates, such as plant debris, algae, water, and soil sediment. The relative abundance of Saprolegniaceae was higher in the cold to cool season than that in the warm to hot season of Korea. This study enhances our understanding of the diversity and ecological attributes of Saprolegniaceae in freshwater ecosystems.